Exploring Constructive Communication in Community Sport: A Systematic Review of the Literature - Fikri, Muhammad Dzul; Sudijandoko, Andun; Purnomo, Mochamad; Priambodo, Anung (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to explore the role of constructive communication in driving community sports through a Systematic Literature Review (SLR) approach. A total of 218 peer-reviewed articles published between 2017 and 2025 in the Scopus database were thematically analyzed to examine how communication contributes to building inclusive, resilient, and empowered sports communities. The findings revealed five major themes: participation and social inclusion, digital transformation and community media, interpersonal skills and leadership, crisis communication strategies, and communication as a tool for social justice. The study highlights that open, empathetic, and collaborative communication not only enhances community engagement but also strengthens inclusive leadership and social resilience. Digital technology plays a significant role in expanding communication channels, although it requires adequate literacy and social sensitivity. The study recommends strengthening interpersonal communication capacities among coaches and facilitators, promoting inclusive use of digital technologies, and implementing continuous evaluation mechanisms to ensure the success of community sports programs